Teknik Lobi Dan Negosiasi Dalam Pengambilan Kebijakan Publik Dan Membangun Hubungan Yang Baik - Aliyah Sofiyani; Fatimah Nisa; Hasna Zhafira; Reyhan Naufal Athaya; Yuanita Ferlinda (CV. ITTC INDONESIA, 2025)
In the public decision-making process, interactions between various parties including the government, private sector, and civil society play a role. In this case, lobbying and negotiation practices serve an important role as a tool to express desires, build agreements, and address differences in interests. Lobbying is no longer seen as an exclusive and often negatively connoted activity, but as an essential element of the democratic system, which allows the involvement of various parties in determining the policies to be implemented. In the public decision-making process, interactions between various parties including the government, private sector, and civil society play a role. In this case, lobbying and negotiation practices serve an important role as a tool to express desires, build agreements, and address differences in interests. Lobbying is no longer seen as an exclusive and often negatively connoted activity, but as an essential element of the democratic system, which allows the involvement of various parties in determining the policies to be implemented. However, there are still many obstacles to the implementation of effective lobbying and negotiation, especially related to transparency, ethics, and availability of information. In addition, not all stakeholders understand how to build good relationships through constructive communication and advocacy. With that background, this journal aims to further explore the role of lobbying and negotiation methods in public decision-making and their contribution to creating harmonious relationships between policy actors. This research is expected to provide practical perspectives and recommendations for professionals, government employees, and activists involved in the policy-making process.